Personality traits, depression and itch in patients with atopic dermatitis in an experimental setting : A regression analysis - Schut, C.; Bosbach, S.; Gieler, U.; Kupfer, J.; Justus Liebig University Giessen (My University, 2013)
It is known that itch is associated with psychological variables, but it is not known whether personality characteristics, depression or anxiety are predictors of experimentally induced itch in patients with atopic dermatitis (AD). In this study itch was induced in 27 patients with AD and 28 healthy controls by the presentation of an experimental video on crawling insects and skin diseases. Itch intensity was measured by self-ratings and by observing the number of scratch movements. Itch increase was determined by subtracting itch intensity induced by the experimental video from itch intensity induced by a control video. Psychological variables were assessed using validated questionnaires. In patients with AD, depression was a significant predictor of self-rated induced itch (corrected R2 = 0.175); while agreeableness and public self-consciousness were significant predictors of induced scratching (corrected R2 = 0.534). In healthy controls no associations were found. These results imply that a special group of patients with AD might benefit from certain psychological interventions.
Keywords: atopic dermatitis; psychodermatology; personality characteristics; depression; anxiety; ddc:610